Self-Help Group Therapy as Community Nursing Intervention to Reduce Stress Response and Increase Self-Efficacy in High-Risk Pregnant Women - Reni Nurhidayah; Prima Dewi Kusumawati (Journal Of Nursing Practice, 2023)
Background: Unexpected and unanticipated obstetric problems that can have a direct or indirect impact on the well-being of mothers and babies are considered high-risk pregnancies. Uncertainty in health conditions is felt as a life-threatening event that can threaten the lives of mothers and babies. This condition will trigger various stress responses felt by the mother. Moderate to severe stress during pregnancy greatly increases the risk of developing postpartum depression. One of the important coping sources to deal with stress is self-efficacy. Personal abilities are all aspects of an individual that can be utilized to solve problems. One of the interventions that can be used to improve coping mechanisms is self-help groups. Self Help group is a group approach to help its members solve their problems. Purpose: This study aims to determine the impact of self-help groups as therapy in the community to reduce stress responses and increase self-efficacy in high-risk pregnant women. Methods: The research design used was a quasi-experimental one-group pre-test post-test design. 15 respondents were given intervention in 3 sessions for 90 minutes in each session. Stress response and self-efficacy were measured before and after the intervention. Data analysis was carried out using the paired sample T-test. Results: This study shows that the average assessment stress response and self-efficacy score of mothers before the self-help group therapy is 128 and 35. After the therapy, the average response stress and self-efficacy score of mothers was 86 and 53. The study shows the effect of self-help group therapy on stress response (?-value = 0,012) and self-efficacy (?-value = 0,021). Conclusion: It was concluded that self-help group therapy was effective in decreasing stress respons and improving self-efficacy for high-risk pregnant women.